2022
DOI: 10.1159/000523731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of In-Centre Haemodialysis Patients between the 1st and 2nd COVID-19 Outbreak in England, Wales, and Northern Ireland: A UK Renal Registry Analysis

Abstract: <b><i>Introduction:</i></b> This retrospective cohort study compares in-centre haemodialysis (ICHD) patients’ outcomes between the 1st and 2nd waves of the COVID-19 pandemic in England, Wales, and Northern Ireland. <b><i>Methods:</i></b> All people aged ≥18 years receiving ICHD at 31 December 2019, who were still alive and not in receipt of a kidney transplant at 1 March and who had a positive polymerase chain reaction test for SARS-CoV-2 between 1 March 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
0
6
1
3
Order By: Relevance
“…Data on testing frequency were not available. It is likely that there was higher testing frequency in the ICHD population [ 14 ], so cases were more likely to be detected than for other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Data on testing frequency were not available. It is likely that there was higher testing frequency in the ICHD population [ 14 ], so cases were more likely to be detected than for other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…But, correct use of personal protective equipment and personnel caring is very important to prevent the infection [9]. One more study compared the 1 st wave and 2 nd wave data on haemodialysis patients saying that risk of death of dialysis patients remains unchanged between the first and second outbreaks and suggested that vulnerable patient group needs to be prioritized for interventions to prevent severe COVID-19 includes vaccination [10]. Previous studies revealed that the infection rate is high in old age subjects, but we found that the age is not significantly associated with positive rate.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Poland from the beginning of the pandemic to January 2021 found that the increase and decrease in the number of new cases occurred first in patients undergoing HD, although the epidemic trajectory was parallel in HD patients and the general population 10 . Likewise, there is a discrepancy in patient prognosis based on the period evaluated, with some studies indicating that mortality was higher in the second wave than in the first 11 , while others found no differences 12 .…”
Section: Introductionmentioning
confidence: 99%